2015
DOI: 10.1155/2015/287906
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Phthiriasis Palpebrarum and Crab Louse: Petrolatum Jelly and 1% Permethrin Shampoo

Abstract: Phthiriasis palpebrarum is an uncommon cause of blepharoconjunctivitis in which Pthirus pubis infest the eyelashes. We report a case of unilateral phthiriasis palpebrarum with crab louse. A 45-year-old man presented with conjunctival hyperaemia and moderate itching associated with irritation, and crusty excretions of the eyelashes in the left eye. Careful slit-lamp examination revealed many lice and nits in left eye and mild conjunctival hyperaemia. No abnormality was found in the right eye. On dermatologic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…In the current study the parasites were observed in both children and adults, it is believed that people in Kurdistan particularly the rural areas havecrowded families live together and in more cases share the same beds with their parents. Cases of Phthiriasis palpebrarum have been reported in countries that have borders with Kurdistan such as Iran and Turkey (Dehghani et al, 2013;Karabela, et al, 2015;Sundu et al, 2015). However, in the records we could not find any studied cases in Kurdistan or Iraq.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In the current study the parasites were observed in both children and adults, it is believed that people in Kurdistan particularly the rural areas havecrowded families live together and in more cases share the same beds with their parents. Cases of Phthiriasis palpebrarum have been reported in countries that have borders with Kurdistan such as Iran and Turkey (Dehghani et al, 2013;Karabela, et al, 2015;Sundu et al, 2015). However, in the records we could not find any studied cases in Kurdistan or Iraq.…”
Section: Discussionmentioning
confidence: 70%
“…Low hygiene, education level and socioeconomicstatus have also been linked to the availability of lice (Mahmood, 2010). Successful treatments of phthiriasis palpebrarum have been achieved using different mechanisms and medications including petroleum Jelly, permethrin, yellow mercuricoxide, vaseline, and recently argon laser (Couch etal., 1982;Jiang et al,2011;Panos et al, 2013;Karabela, et al, 2015;Sundu et al, 2015). In the current study, a special fine forceps was used followed by erythromycin eye ointment and it was successful in eradication of the parasites from the eyes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Phthiriasis palpebrarum in adults is usually associated with pubic hair infestation [ 6 ]. In children, it is usually isolated as in this case because of the lack of terminal hairs on most of their body regions.…”
Section: Discussionmentioning
confidence: 99%
“…Pthirus pubis belongs to the phylum Arthropoda, the class Insecta and the order Phthiraptera. Two other subspecies of lice known to infest humans are Pediculus humanus capitis (head louse) and Pediculus humanus corporis (body louse) (19). Adult pubic lice are typically 1-2 mm in size and wingless with a broad, flat translucent body through which freshly ingested blood may be observed.…”
Section: Discussionmentioning
confidence: 99%